Are the Jameson Land muskoxen, Northeast Greenland, in decline? - Gaidet, Nicolas; Daufresne, Tanguy (Rangifer, 2019)
The Jameson Land region contains the largest muskox population in Northeast Greenland. In the period 1980-1990, late winter population size averaged 3,645. A late winter 2000 survey estimated ca. 1,705 muskoxen. Although no further late winter surveys for muskox abundance have occurred since, there have been two summer bird surveys, which recorded incidental observations of muskoxen, i.e., 607 in 2008 and 610 in 2009. We report on muskox observations obtained in a subarea of Jameson Land during the summer 2016 ground survey for birds. Although in the 1982-2000 period this subarea averaged 1,153 ± 346 muskoxen, we observed 138 individuals and a low calf number. The few muskoxen observed and poor calf production suggest population decline. We briefly discuss possible factors that could influence muskox mortality and population abundance. Surveys specific to muskoxen are necessary to ascertain current population abundance, demographics and trend.